Parent viewership of 13 reasons why and parental perceived knowledge about adolescent life: implications for parental efficacy among parents from the United States, the United Kingdom, Brazil, and Australia/New Zealand. Issue 2 (3rd April 2022) - Mann, Supreet; Cingel, Drew P.; Lauricella, Alexis R.; Wartella, Ellen
ABSTRACT: There has been a recent increase in television programming that aims to provide realistic portrayals of adolescent life in an effort to both entertain and educate adolescent viewers. Research on this entertainment-education programming has examined the effects on adolescent viewers; however, it has not considered the relationship between parent viewing of such programming and their perceived knowledge about adolescent life. Further, it is possible that parent viewing of entertainment-education programming can relate to parental efficacy indirectly via their perceived knowledge about adolescent life. We test these relationships using data from 1, 880 parent viewers and non-viewers (adolescent children ages 13–17) of the series 13 Reasons Why sampled from Brazil, Australia/New Zealand, the United States, and the United Kingdom. Results suggest an indirect relationship between parent viewership of the series and parental efficacy, via parental perceived knowledge, among parents who viewed the entire first season in comparison to those who only viewed some episodes. There were direct relationships between viewing and parental efficacy when comparing those who viewed all episodes to non-viewing parents. These findings suggest that entertainment-education programming may relate to positive outcomes among parents, with implications for the family ecology. IMPACT SUMMARY a. Prior State of Knowledge: The genre of entertainment-education programming (EE) includes programs that provide realistic portrayals of adolescent life including portrayals of sensitive topics. Prior examinations of adolescent-directed EE consider effects on adolescent viewers but do not consider the effect on parent viewers. b. Novel Contributions: Results suggest an indirect relationship between parent viewership of the Netflix produced series, 13 Reasons Why, and parental efficacy, via parental perceived knowledge. These findings occur among parents who viewed the entire first season of the series in four global regions. c. Practical Implications: These findings suggest that EE programming may relate to positive outcomes among parent viewers and have larger implications for the family ecology by bolstering parental efficacy and perceived knowledge about adolescent life.